Social responsibility practices in the public sector – the case of local companies in Portugal - Pina, Solângela; Costa, Cláudia S.; Monte, Ana; Maia, Tânia Sofia Vieira; Correia, Pedro Miguel Alves Ribeiro; Resende, Sérgio André Lopes (Revista da FAE, 2023)
In today’s business world, social responsibility is crucial because many societal issues stem from companies’ actions. Therefore, it is essential to have socially responsible companies that support sustainable development principles and strive to create a fairer and more equitable society in economic, social, and environmental aspects. To ensure transparency, companies should share both positive and negative impacts achieved through sustainable practices in a sustainability report for their stakeholders. This paper analyzes the sustainability reports of public-local companies in Portugal using the Global Reporting Initiative (GRI) indicators to evaluate their social responsibility practices. The analysis